Epigenetic Mechanisms in Neuroendocrine Neoplasms: Is There a Place for Inhibitors of DNA Binding Proteins? - David Sanchis-Pascual; María Isabel Del Olmo-García; Pilar Morillas-Amat; Stefan Prado-Wohlwend; Ángel Segura Huerta; Juan Francisco Merino-Torres (Frontiers in Bioscience-Landmark)
Inhibitors of DNA-binding (Id) proteins constitute a family of repressor factors that modulate a multitude of cellular processes and have been linked to tumor aggressiveness, resistance to chemotherapy, angiogenesis, and worse prognosis in numerous malignancies. This review explores the role of Id proteins in the pathogenesis of neuroendocrine neoplasms (NENs). The findings revealed that this family of proteins shows significant overexpression in tumors such as small cell lung carcinoma (SCLC), neuroendocrine prostate carcinoma (NEPC), and medullary thyroid carcinoma (MTC), although the role of epigenetics in regulating Id proteins within NENs remains poorly understood, with most evidence limited to NEPC. These results underscore the potential of Id proteins not only as diagnostic biomarkers and promising therapeutic targets for the management of NENs, but also highlight the need for further research to better understand their epigenetic regulation and broader role in these tumors.